Identification of HOTS Creative Thinking, Science Process Skills and Digital Literacy in Physics Subject - Astalini Astalini; Darmaji Darmaji; Dwi Agus Kurniawan; Minarsih Minarsih (Universitas Negeri Surabaya, 2022)
High Order Thinking Skills (HOTS) creative thinking, science process skills and digital literacy of students are important components in learning, especially learning physics. The purpose of this study was to find out how High Order Thinking Skills creative thinking, science process skills and digital literacy of students at SMAN 8 Muaro Jambi. The data collection instrument used a question sheet for HOTS creative thinking, an observation sheet for science process skills and a questionnaire for digital literacy. The data analysis in this study was quantitative using descriptive statistics and qualitative using Miles & Huberman. The results of the data obtained are then grouped using a Likert scale. The flow of this research is to prepare instruments and interview sheets, conduct interviews with teachers and students, distribute instruments, analyze data and obtain data results. The results of this study are HOTS, KPS and digital literacy in class X MIPA 5 are greater than X MIPA 3 with successive values ​​in class X MIPA 5 are 80.25, 83.20 and 72.87 while class X MIPA 3 is 80.69, 85.40 and 74.81. So from these data it can be seen that the ability of students to think creatively increases in line with science process skills and digital literacy and vice versa. Science process skills help improve students' creative thinking skills by using practicum-based learning. Digital literacy helps students to get various kinds of physics learning resources, materials, modules, questions and exercises. Digital literacy also helps students to do online practicum by utilizing digital media and the web. So that the creative thinking skills, science process skills and digital literacy skills of students influence each other.